GAMBARAN KARAKTERISTIK DAN PENGETAHUAN IBU YANG MEMPUNYAI BAYI USIA 7-12 BULAN TENTANG PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS AIR DINGIN KELURAHAN AIA PACAH KOTA PADANG TAHUN 2018 - nila eza fitria (JURNAL KESEHATAN MERCUSUAR, 2019)
Mother's milk (ASI) plays an important role to maintain the health and survival of babies. The low level of exclusive breastfeeding based on the Ministry of National program is 40% and 30% due to the factors of maternal age, employment, education, and husband's support. Based on data from the Padang City Health Office the working area of ​​the Air Dingin health center is the lowest percentage (33.85%). The purpose of this study was to determine the characteristics and level of knowledge of mothers who have babies aged 7-12 months about exclusive breastfeeding in the working area of ​​cold water puskesmas in Aia Pacah village, Padang city in 2018.This type of research is descriptive. This research was conducted in August 2018 in Aia Pacah Village, Padang City. The study population was all mothers who had babies aged 7-12 months in the Aia Pacah village, Padang. The sample in this study was 68 people with total sampling technique. Using primary data. Data collection was carried out by filling out questionnaires and filling out informed consent. Data processing techniques for editing, coding, entry and cleaning. Data analysis is carried out univariately. The results showed that of the 68 respondents who had ASI production age were not at risk as many as 52 people (76.4%), respondents who had ASI production age were at risk as many as 16 people (23.5%) giving exclusive breastfeeding, respondents who had as much higher education 45 people (66.1%), respondents who have a low education level of 23 people (33.8%), respondents who work as many as 22 people (32.2%), respondents who do not work as many as 46 people (67.6% ), respondents with high knowledge were 32 people (47.0%) and respondents with low knowledge as many as 36 people (52.9%).From the data above, it can be concluded that most mothers have breast milk production age not at risk in exclusive breastfeeding. More than half of mothers who have babies aged 7-12 months do not work. More than half of mothers who have higher education in exclusive breastfeeding. More than half of mothers who have a low level of knowledge in exclusive breastfeeding.